Worker's movement in Iloilo city, 1970-1999 - Estocapio, Rene C.
The study analyzes the course of development of workers' struggles in Iloilo City from the 1970 to 1999. It tries to give a general overview of what was happening in Iloilo City labor front throughout the last three decades of the 20th century. More specifically, the study describes the economic and political environment that affects and influence the condition of the Iloilo working class; identifies the various organizations formed by the workers as response to various issues and problems affecting them; describes the different viewpoints of these organizations in dealing with workers issues; describes the dynamics of these organizations; and determines the various forms of struggles employed by the workers in pursuance of their perceived goals and objectives., The study views the workers' movement in Iloilo City as an integral part of the class struggles that exist in present society. It recognizes and employs the Marxist analysis of political struggle and social change as the best instrument in understanding the workers' movement in its entirety. The workers' movement in Iloilo City grow as a continuous response of workers to exploitation in the workplace, to the curtailment of their rights to work and to earn a just wage, and to their ever-worsening misery. The workers formed organizations to have a collected strength to protect their rights and to advance their economic and political interest in the midst of a generally hostile and oppressive environment. Each worker's group has a distinct viewpoint and analysis of workers issues and this viewpoint guides the workers on what methods of struggle they will employ in advancing their interest. Generally, two kinds of workers' groups existed in Iloilo City. One kind is the militant workers' group that combines economic and political struggle up to the point of demanding for radical social change. The other kind of workers' group is the conservative and moderate workers' group that focuses primarily on workers' economic welfare and opposes a radical change of society. One workers' group competes with the other for dominance in the Iloilo City labor front. This competition impedes the creation of a united front of workers but it has also strengthens the capabilities of each workers' group to be more responsive to workers' issues and interests. The study is a contribution to academic research on local history, to a more profound understanding of workers' struggles, and to the dynamics and development of political movements existing in the country today.